ANCAMAN BAGI PEMBUAT GAMBAR DAN PATUNG DALAM HADIS MENURUT AHMAD HASSAN - Repa Hudan Lisalam (Jurusan Ilmu Hadis Fakultas Ushuluddin, Dakwah dan Adab UIN Sultan Maulana Hasanuddin Banten, 2022)
Abstrac: This article discusses the thoughts of A. Hassan regarding the meaning of the hadith which contains the threat of punishment in the afterlife for the maker of ṣūrah (image or statue). The aim is to find out the method used by A. Hassan in understanding the hadith. The method used in this article is library research, namely by collecting various writings in the form of books and journals from relevant previous research. The results of this study are that the method used by A. Hassan in understanding the hadith about ṣūrah is al-jam'u wa at-taufiq, namely by compromising between the hadith containing threats to the maker of ṣūrah with the hadith containing the Prophet's permission to Aisyah to play with dolls and make pillows from picture cloth. In addition, A. Hassan also tends to use a socio-historical approach when understanding the hadith about ṣūrah so that A. Hassan in the end concludes that the threat contained in the hadith of the Prophet for the maker of ṣūrah is limited to images or statues that have the potential to be worshiped or made into idols given that many Muslims at that time were previously idol worshippers. Thus the threat in the hadith is a form of Islamic preventive action so that Muslims at that time do not fall back into the practice of worshiping idols like in the jahiliyyah period.